Beyond the border : young minorities in the Danish-German borderlands, 1955-1971 - Wung-Sung, Tobias de Fønss, 1980- 1980- (Berghahn, 2019)
"In the nineteenth century, the hotly disputed border region between Denmark and Germany was the focus of an intricate conflict that complicates questions of ethnic and national identity even today. Beyond the Border reconstructs the experiences of both Danish and German minority youths living in the area from the 1950s to the 1970s, a period in which relations remained tense amid the broader developments of Cold War geopolitics. Drawing on a remarkable variety of archival and oral sources, the author provides a rich and fine-grained analysis that encompasses political issues from the NATO alliance and European integration to everyday life and popular culture"--